HCC in 2010; are we offering appropriate therapy?. (13th March 2011) - Short, J; Blackwell, E; James, M
Abstract : Introduction: Hepatocellular carcinoma (HCC) cases are increasing in UK, related to rising prevalence of chronic liver disease and immigration from areas endemic for viral hepatitis. Treatment options for HCC include local ablative therapy (eg, RFA), transarterial chemoembolisation (TACE), surgical resection, liver transplantation and oral multikinase inhibitors in compassionate use or clinical trials. Barcelona Clinic for Liver Cancer (BCLC) staging includes disease volume, hepatic synthetic function and performance status. The authors examined whether patients received appropriate treatment according to BCLC stage.1 2 Methods: All cases of HCC managed during 2009 were identified from the Mid-Trent Hepatobiliary Cancer MDT registry and from radiology, pathology and liver resection databases. Patient demographics, disease aetiology, Child-Pugh score, mode of HCC diagnosis and BCLC stage were determined. Results: 41 HCC cases were identified during 2009. 33 were males (80%) and median (range) age was 69 (21–92) years. 20 (49%) patients had underlying alcoholic liver disease, 6 (15%) NASH cirrhosis, 5 (12%) HBV and 2 (5%) HCV infection. 8 (20%) had either no known underlying liver disease or cryptogenic cirrhosis. Child-Pugh classification A/B/C was found in 29/9/3 patients. HCC surveillance using ultrasound scanning (USS) and/or AFP estimation identified 13 (32%) cases. Definitive HCC diagnosis was by CT or MR imaging in 24 (59%) and CT/MR imaging and biopsy in 17 (41%). Median (range) AFP at diagnosis was 21 (1–100 000) ng/ml. Median (range) time from diagnosis to MDT assessment was 2 (1–26) weeks and from MDT to first treatment 4 (1–26) weeks. BCLC stage (and treatment) was 0; very early stage, n=1 (1 RFA), A; early stage, n=11 (3 resection/3 RFA/4 TACE/1 symptomatic), B; intermediate stage, n=22 (1 resection/2 RFA/14 TACE/5 symptomatic), C; advanced stage, n=4 (1 RFA/1 TACE/2 symptomatic), D; terminal stage, n=3 (3 symptomatic). 35 (85.4%) patients were treated according to BCLC recommendations. 18 (44%) patients remain alive after median (range) follow-up of 11 (1–36) months. Conclusion: Over 85% of patients identified with HCC were managed according to BCLC recommendations. However, most cases (68%) were identified outside of screening programmes and over 70% were intermediate or higher BCLC stages. Detection at earlier stages with targeted surveillance may improve outcomes, although 20% had no known underlying liver disease. Therapeutic trials are required to investigate more effective therapies in those with advanced disease.